A cultural model of infidelity among African American and Puerto Rican young adults. - Macauda, Mark M; Erickson, Pamela I; Singer, Merrill C; Santelices, Claudia C (Anthropology & medicine, 2011)
Having concurrent sexual partners is a risk factor for STIs and HIV/AIDS, yet few studies have investigated the cultural meanings and functions of concurrency. A multi-method qualitative/quantitative study of sexual ideas, attitudes, and behaviors among inner-city Puerto Rican and African American emergent adults (age 18-25) in Hartford, Connecticut, USA, suggests that having concurrent partners is common in this population. Using data from 12 focus groups and 40 participants in systematic data collection techniques (e.g., pile sorts), the underlying cognitive structure of concurrency and cheating/infidelity are explored. Results suggest that participants are less tolerant of multiple partners in more committed relationships, but that very few relationships can be considered committed. Furthermore, participants see cheating as inevitable even in committed relationships. Sexual transgressions are considered the most severe form of cheating. Having an outside partner for emotional reasons or to have access to one's child were seen as more acceptable/forgivable than doing so for sexual satisfaction, social status or material goods. Multiple partnerships must be seen in the context of the inner city where resources and opportunities are scarce and young adults attempt to protect themselves from emotional injury. Documenting new and changing social constructions of infidelity is important for understanding the social context of sexual behavior in our global world and for designing culturally appropriate health interventions.
Keywords: Adolescent; African Americans; Anthropology, Medical; Cluster Analysis; Female; Focus Groups; Hispanic Americans; Humans; Male; Models, Psychological; Puerto Rico; Reproductive Health; Sexual Behavior; Sexual Partners; Urban Population; Young Adult